EVOLUTION OF PRIVATIZATION AND DEPUTY OF STATE IN THE INDUSTRIAL SECTOR OF UZBEKISTAN - Khusainov Ravshan Rakhimovich (Scholar Express Journals, 2023)
In the article, the author pays special attention to the features of privatization, denationalization and, on the basis of this, to create multi-structural ownership, privatization models, and the formation of a market economy
Keywords: privatization; denationalization; market conditions